Problem-based learning: design of a DC motor driver for combat robots - dos Santos, Bruno Henrique; Cartier, Ruan; Silva, João Pedro; Melo, Guilherme; de Oliveira Neto, José; Cajueiro, João (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
In this paper, we describe the use of problem-based learning in the project of a DC driver motor board for combat robot competitions. For that, a team of students from different engineering courses work together to acquire knowledge related to electrical circuits design, C program language for microcontrollers, and printed circuit board manufacturing.